Pengelolaan Media Sosial pada Usaha XYZ - Nuraini Arifianti; Nunuk Adiarni (AGRIBUSINESS JOURNAL, 2019)
The social media is currently not only used for social friendship but also for business purpose.The people use line, whatshapp, instagram and facebook. Related to business goals, the content is made possible by availability of the applications to convey marketing messages to customers. This requires creative message and content creators, which work in team with decision maker and administrator. However, it’s need  to continuously manage it. This study was aimed to find out how the management of social media in XYZ businesses using descriptive qualitative. Instagram management implemented by XYZ starts from setting target customers to the content evaluation process. However, it has not comprehensively been managed unless it responds to negative comments from followers. The results of the study prove that using the social media such as Instagram in marketing requires management by planning, organizing and decision making process for creative content and followed by an evaluation and handling follower responses.